Analisis Peran Teknologi 4.0 Sebagai Pembantu Bisnis Bagi Masyarakat - Devia Ananda Umar; Dicky Wahyudi; Nur Riswandi Marsuki (Concept: Journal of Social Humanities and Education, 2024)
The development of technology 4.0 has a very positive impact on society. Industry 4.0 emphasizes the concept of digitalization that is consistent and connects all productive components of the economy. Several technologies are helping Industry 4.0, such as cloud, simulation, augmented reality, robots, internet of things, big data analytics, additive manufacturing, and cybers ecurity. The method used in this article is literature study, which means data collection to understand and study the theories discussed in the relevant literature. Literature research helps to understand the conceptual framework of a topic and find theoretical foundations for further research. The research also helps guarantee that current research takes into account previous work and fills knowledge gaps. For this study, internet searches and documentation studies were used to collect data. The result is that Technology 4.0 not only helps businesses but also improves the economy and people's welfare. Technology 4.0 greatly helps businesses by increasing global access, improving operational efficiency, driving innovation, and improving product safety. To ensure that the benefits of this technology are felt by everyone, society must continue to take this technology with caution while addressing issues such as data security and inequality of access to technology. Keywords: T, Business, Society